Tunneling anisotropic magnetoresistance driven by magnetic phase transition - X. Z. Chen (Nature Portfolio, 2017)
Tunneling anisotropic magnetoresistance is promising for next generation memory devices but limited by the low efficiency and functioning temperature. Here the authors achieved 20% tunneling anisotropic magnetoresistance at room temperature in magnetic tunnel junctions with one α′-FeRh magnetic electrode.